The role of glucose in cognition, risk of dementia, and related biomarkers in individuals without type 2 diabetes mellitus or the metabolic syndrome: A systematic review of observational studies. (April 2022) - Kirvalidze, Mariam; Hodkinson, Alexander; Storman, Dawid; Fairchild, Timothy J.; Bała, Malgorzata M.; Beridze, Giorgi; Zuriaga, Ana; Brudasca, Nicoleta I.; Brini, Stefano
Abstract: Background: Excessive blood glucose promotes neuropathological cognitive decline in individuals with type 2 diabetes mellitus and the metabolic syndrome, but no systematic synthesis of the evidence for the same association exists in individuals without these conditions. Objectives: To systematically review studies exploring the role of glucose on cognition, dementia risk, and related biomarkers in adults without diabetes or metabolic syndrome. Data sources: We searched databases from inception until July 2021 and manually searched the reference lists of included studies. Risk of bias was assessed using the Joanna Briggs Institute tool. Results: We found 46 observational studies including approximately 98, 216 participants. Substantial heterogeneity in study results precluded drawing definitive conclusion whether blood glucose levels are associated with cognition or dementia risk. Higher blood glucose, however, was associated with greater amyloid burden, brain atrophy, and reduced cortical thickness. Conclusions and implications: High glucose concentrations in blood may exacerbate dementia-related neuropathology but whether this translates into pathological cognitive decline or elevate dementia risk later in life remains unclear. Highlights: Glucose can negatively impact cognition and increase dementia risk in individuals with diabetes or the metabolic syndrome. No systematic synthesis of the same association has been conducted in individuals without these conditions. We reviewed studies exploring the role of glucose in cognition, dementia risk, and related brain biomarkers. The high degree of methodological heterogeneity precluded drawing conclusions related to cognitive decline/dementia risk. High blood glucose concentrations were associated with greater dementia-related neuropathology.